Modern GFRP composite footbridges - Pyrzowski, Łukasz; Miśkiewicz, Mikołaj (International Conference “Environmental Engineering”, 2017)
Application of GFRP composites in civil engineering is still not large but already noticeable. Advantages of this material, such as: low volume weight, relatively high stiffness and strength, well fatigue resistance, easiness in shaping, high material damping and high environmental resistance, make it attractive for bridge and in particular foot bridge designers. It is estimated that nowadays in the world there are realized hundreds of bridges, the construction of which, whole or in part is made of GFRP. Most of them are small span structures. However, it is possible to find some interesting designs. The paper presents an overview of the most spectacular examples of footbridge structures, in which the GFRP materials plays a key role. The few examples are: Aberfeldy Footbridge in Scotland, the world's largest structure of this kind; Lleida Pedestrian Bridge, the longest arch bridge made out standard GFRP pultruded profiles or EXPO Footbridge in Lisbon, truss bridge of 30 m span length. The last example is the footbridge designed and con structed by polish consortium Fobridge. The footbridge, which arose as a result of scientific project was studied in a great details taking into account, among others: material testing, validation studies and load tests.
Keywords: modern materials; GFRP composite; footbridges